Pola Komunikasi Organisasi dalam Membangun Kualitas Kinerja Karyawan: Studi Kasus pada PT Rajawali Anugerah Jaya - Saputra, Diki Rachmat; Delima, Isniyunisyafna Diah; Yoman, Mad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze organizational communication patterns in building employee performance quality at PT Rajawali Anugerah Jaya. Company communication patterns will have an impact on employee performance, depending on whether organizational communication that occurs is running well or not. This study uses a qualitative descriptive approach with a case study method. The data used through interviews, observations, and documentation to superiors and employees of PT Rajawali Anugerah Jaya. This study uses the theory of Human Relations put forward by Elton Mayo in 1933. The results of the study show that PT Rajawali Anugerah Jaya in building employee performance quality uses vertical communication, this communication flow is very effective in sending and receiving messages in a company. The factors causing obstacles that occur at PT Rajawali Anugerah Jaya are semantic obstacles and technical obstacles.